2015
DOI: 10.1039/c5nj01821h
|View full text |Cite
|
Sign up to set email alerts
|

An anti-biodegradable hydrophobic sulfonate-based acrylamide copolymer containing 2,4-dichlorophenoxy for enhanced oil recovery

Abstract: We report here a novel anti-biodegradable hydrophobic acrylamide copolymer that was prepared from acrylamide, acrylic acid, sodium 3-(allyloxy)-2-hydroxypropane-1-sulfonate and N-allyl-2-(2,4dichlorophenoxy) acetamide using the 2,2 0 -azobis(2-methylpropionamide) dihydrochloride initiation system. Subsequently, the copolymer was characterized by FT-IR, 1 H NMR, TG-DTG and watersolubility. And the biodegradability test indicated that the copolymer was not deemed to be readily biodegradable via a closed bottle t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…6(b), when the concentration of polymer solution is lower than the critical association concentration (CAC), the growth rate of viscosity in HPAM was slightly higher than that in PMAD and h-PMAD, with a linear viscosity-concentration relationship. According to the literature, 35 under CAC the association of hydrophobic groups mainly occurs intra-molecularly, and the contribution to viscosity is far less than the electrostatic repulsion of carboxylate ions from HPAM. However, when the concentrations exceeded CAC, the viscosities of the PMAD and h-PMAD were much higher than that of HPAM, exhibiting a power-law exponential growth.…”
Section: Thickening Ability and Water Solubilitymentioning
confidence: 99%
See 2 more Smart Citations
“…6(b), when the concentration of polymer solution is lower than the critical association concentration (CAC), the growth rate of viscosity in HPAM was slightly higher than that in PMAD and h-PMAD, with a linear viscosity-concentration relationship. According to the literature, 35 under CAC the association of hydrophobic groups mainly occurs intra-molecularly, and the contribution to viscosity is far less than the electrostatic repulsion of carboxylate ions from HPAM. However, when the concentrations exceeded CAC, the viscosities of the PMAD and h-PMAD were much higher than that of HPAM, exhibiting a power-law exponential growth.…”
Section: Thickening Ability and Water Solubilitymentioning
confidence: 99%
“…Obviously, polymers PMAD and h-PMAD exhibited more solubility at higher conductivity values all the time and a shorter steady time of 80 min and 72 min, respectively, compared to HPAM (90 min), which is due to the presence of the carboxylate ion, and the quaternary ammonium and glycol sulte from MMPES made the molecules more soluble. 35 This theory only conrms why h-PMAD ha a shorter steady time than PMAD, originating from its large number of carboxylate ions.…”
Section: Thickening Ability and Water Solubilitymentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that a small population of ionic or nonionic surfactants, such as sodium dodecyl sulfate and poly(vinyl alcohol), show a very strong synergy with various polymers in solution . In our previous work, we made many attempts to modify the structures of polyacrylamides to retain their excellent performance under high‐temperature and high‐salt conditions . The results indicate that polymers containing a rigid aromatic ring on the side chains can provide a π–π stacking point and exhibit outstanding shear stability, but their apparent viscosity retention rates are less than 40% when the temperature rises from 30 to 120 °C .…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Recently, hydrophobic associating polymers have been widely used in oileld applications, such as acidizing treatments, 7,8 drilling and completion uids, and polymer ooding. [9][10][11][12] In oileld applications, the hydrophobic associating polymer is adsorbed on the reservoir for the interaction of the polymer and the reservoir, which may have some effect on the reservoir. The adsorption behavior of hydrophobic associating polymers has attracted signicant attention from many researchers.…”
Section: Introductionmentioning
confidence: 99%